2014
DOI: 10.3109/17483107.2014.921843
|View full text |Cite
|
Sign up to set email alerts
|

Sit-to-stand transfer mechanics in healthy older adults: a comprehensive investigation of a portable lifting-seat device

Abstract: Purpose: To evaluate lower extremity mechanics and muscle activation associated with the sit-to-stand transfer using a portable lifting-seat device and to compare these data to an unassisted transfer in healthy young and older adults. Methods: Bilateral lower extremity and low back musculature electromyography, three-dimensional leg and trunk motion, and ground reaction forces were recorded from 10 young (mean age = 25) and 10 older (mean age = 69) adults during five trials of (i) no assist and (ii) assisted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
3
4
1
Order By: Relevance
“…The total STS time in the N condition (2.2 ± 0.3 s) was similar to that reported by Kuo et al, Millington et al, and Rutherford et al [7,12,23]. Compared with the method used in the present study for defining each movement phase of the STS and BTS movements, Mourey et al [11] determined the start and end points of the motion in accordance with a change of the exceeding a threshold of 10% of the peak forward angular velocity of the trunk.…”
Section: Time Of Sts and Btssupporting
confidence: 89%
See 4 more Smart Citations
“…The total STS time in the N condition (2.2 ± 0.3 s) was similar to that reported by Kuo et al, Millington et al, and Rutherford et al [7,12,23]. Compared with the method used in the present study for defining each movement phase of the STS and BTS movements, Mourey et al [11] determined the start and end points of the motion in accordance with a change of the exceeding a threshold of 10% of the peak forward angular velocity of the trunk.…”
Section: Time Of Sts and Btssupporting
confidence: 89%
“…Moreover, among the old nonfallers and old fallers, the old fallers had a lower muscle power and required a longer time to leave their seat. Rutherford et al [7] found that the hip and knee joint angles of the elderly were significantly greater than those of young adults while standing up. The elderly also showed greater activity of the lower extremity muscles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations